Pembentukan Karakter Disiplin Melalui Pembiasaan Sholat Dhuha di Madrasah Ibtidaiyyah - Mursid Mursid; Aisyah Sisilia Pratyaningrum (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
The habit of performing Dhuha prayer is one of the efforts to instill discipline in students. Dhuha prayer is a voluntary act of worship performed in the morning after sunrise. Through this habit, students are taught to commit time to worship, instilling values of patience and discipline in carrying out daily routines. By repeatedly performing Dhuha prayer, students will learn to manage their time well, which can influence their discipline in daily activities, including attendance and punctuality at school. Additionally, consistent religious practices foster spiritual awareness, improve morals, and help students steer away from undesirable behaviors. However, it's essential to remember that forming discipline in students depends not only on the habit of Dhuha prayer but also requires consistent support and guidance from teachers, parents, and the entire environment.